Plane Wall Effect of Flow around Two Circular Cylinders in Tandem Arrangement - Triyogi Yuwono; Wawan Aries Widodo; Heru Mirmanto; Fahmi Fahreza (IPTEK The Journal for Technology and Science, 2011)
The flow characteristic around two circular cylinders in tandem arrangement located near a plane wall were investigated experimentally in a uniform flow at a Reynolds Number of 5.3 x 104. The center to center spacing between the two cylinders relative to the cylinder diameter was constantly maintained at P/D = 1.5. The pressure distributions along the surface of the cylinder and the plane wall were measured by varying the gap-to-diameter of cylinder ratio (G/D) in the range of 0 < G/D < 0.467. Surface oil-film techniques were used to investigate the flow patterns on the cylinder. The result showed that for upstream cylinder, in the gap-to-diameter ratio G/D < /D, there is no stagnation point at front side of the upstream cylinder; it is gradually raised as the gap increase. For the downstream cylinder, a peak on the lower side of the front side of the cylinder is apparent in each of the pressure distributions. This peak represents the reattachment of shear layer that separates from lower side of the upstream cylinder. The reattachment point tends to move forward close to the angular position of  = 0o as the gap ratio increase. The shear layer bifurcates into two shear layers. One shear layer continues in the downstream direction, and the other shear layer flows in the upstream direction.